Antimicrobial resistance determinants are associated with Staphylococcus aureus bacteraemia and adaptation to the healthcare environment: a bacterial genome-wide association study. Issue 11 (23rd November 2021) - Young, Bernadette C.; Wu, Chieh-Hsi; Charlesworth, Jane; Earle, Sarah; Price, James R.; Gordon, N. Claire; Cole, Kevin; Dunn, Laura; Liu, Elian; Oakley, Sarah; Godwin, Heather; Fung, Rowena; et al.
Abstract : Staphylococcus aureus is a major bacterial pathogen in humans, and a dominant cause of severe bloodstream infections. Globally, antimicrobial resistance (AMR) in S. aureus remains challenging. While human risk factors for infection have been defined, contradictory evidence exists for the role of bacterial genomic variation in S. aureus disease. To investigate the contribution of bacterial lineage and genomic variation to the development of bloodstream infection, we undertook a genome-wide association study comparing bacteria from 1017 individuals with bacteraemia to 984 adults with asymptomatic S. aureus nasal carriage. Within 984 carriage isolates, we also compared healthcare-associated (HA) carriage with community-associated (CA) carriage. All major global lineages were represented in both bacteraemia and carriage, with no evidence for different infection rates. However, kmers tagging trimethoprim resistance-conferring mutation F99Y in dfrB were significantly associated with bacteraemia-vs-carriage ( P= 10 -8.9 -10 -9.3 ). Pooling variation within genes, bacteraemia-vs-carriage was associated with the presence of mecA (HMP=10 -5.3 ) as well as the presence of SCCmec (HMP=10 -4.4 ). Among S. aureus carriers, no lineages were associated with HA-vs-CA carriage. However, we found a novel signal of HA-vs-CA carriage in the foldase protein prsA, where kmers representing conserved sequence allele were associated with CA carriage ( P= 10 -7.1 -10 -19.4 ), while in gyrA, a ciprofloxacin resistance-conferring mutation, L84S, was associated with HA carriage ( P= 10 -7.2 ). In an extensive study of S. aureus bacteraemia and nasal carriage in the UK, we found strong evidence that all S. aureus lineages are equally capable of causing bloodstream infection, and of being carried in the healthcare environment. Genomic variation in the foldase protein prsA is a novel genomic marker of healthcare origin in S. aureus but was not associated with bacteraemia. AMR determinants were associated with both bacteraemia and healthcare-associated carriage, suggesting that AMR increases the propensity not only to survive in healthcare environments, but also to cause invasive disease.